Maintaining Religious Harmony Through Collaboration Strategies - Zainul Abas; Abdul Ghofur (Indonesian Journal of Islamic Literature and Muslim Society, 2021)
Religious harmony is threatened by anti-tolerance groups. Therefore, religious communities and local governments continue to strive to build religious harmony. However, a collaboration between them is still sporadic and incidental. The relationship between these institutions has not been running in a systemic and sustainable manner. This article aims to describe and analyze the efforts of the Forum for Religious Harmony (FKUB) to maintain religious harmony in Solo Raya, Indonesia, from 2015 to 2019. This study concludes that creating systemic and sustainable collaboration between religious institutions and government agencies is very important to intensify and maximize efforts to build and maintain religious harmony. Systematic and sustainable collaboration requires cooperation between these institutions. Thus, all fields will run normally and productively. This research contributes to developing a theory of conflict resolution in multi-religious societies. In addition, this research is also useful in developing problem-solving strategies, especially related to inter-religious conflicts and concern for religious harmony in the future.